2013
DOI: 10.1126/science.1231345
|View full text |Cite
|
Sign up to set email alerts
|

A Functional [NiFe]Hydrogenase Mimic That Catalyzes Electron and Hydride Transfer from H 2

Abstract: Chemists have long sought to mimic enzymatic hydrogen activation with structurally simpler compounds. Here, we report a functional [NiFe]-based model of [NiFe]hydrogenase enzymes. This complex heterolytically activates hydrogen to form a hydride complex that is capable of reducing substrates by either hydride ion or electron transfer. Structural investigations were performed by a range of techniques, including x-ray diffraction and neutron scattering, resulting in crystal structures and the finding that the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
214
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(224 citation statements)
references
References 27 publications
(9 reference statements)
5
214
1
2
Order By: Relevance
“…In that structure, as was hypothesized by past enzyme and model studies [1,7,[10][11][12][13], where Ni-SIa is defined as '0' [7]. For example, the hydride species, Ni-R, is placed at the 14.…”
Section: Structures and Functions Of Hydrogenasesmentioning
confidence: 95%
See 2 more Smart Citations
“…In that structure, as was hypothesized by past enzyme and model studies [1,7,[10][11][12][13], where Ni-SIa is defined as '0' [7]. For example, the hydride species, Ni-R, is placed at the 14.…”
Section: Structures and Functions Of Hydrogenasesmentioning
confidence: 95%
“…The literature includes reports of numerous [NiFe]H 2 ase model complexes, but heterolytic cleavage of H 2 molecules using the NiFe complexes was only accomplished in 2013 [11,12]. Since the acetonitrile (CH 3 CN) ligand in the Ni-SIa model shown in Fig.…”
Section: H 2 Activation By [Nife]h 2 Ase Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…In both maps, positive neutron scattering-length density was observed between the Ni and Fe atoms. Although the final R value (0.2581 for 931 I > 2σ(I) reflections) was higher than that in typical single-crystal neutron structure analysis of a metal complex because of the quality of the sample crystal, these Fourier maps strongly suggested that the [NiFe] model complex has the expected Ni(μ-D)Fe structure [148]. iBIX was originally designed for structure analyses of bio-macromolecules, and its sample environment was optimized for fragile and air-sensitive protein crystals.…”
Section: Neutron Structure Analysis Of a [Nife]hydrogenase-mimicking mentioning
confidence: 67%
“…Even though some of these systems might actually be amenable to studies with EPR spectroscopy, very little information is available in that direction [35][36][37]. The catalytic conversion of H 2 to protons and electrons has remained a challenging task with such structural mimics [39][40][41][42][43]. A second approach that takes functional inspiration from hydrogenases has also been successful in this regard [43][44][45][46].…”
Section: Activation Of Dihydrogenmentioning
confidence: 97%